Comparação entre o uso de Prompts Instrucionais e o estudo autodirigido na competência diagnóstica de arritmias cardíacas supraventriculares em estudantes de medicina - Mello, Ricardo Negri Bandeira de (2019)
Introduction: Studies on the teaching of electrocardiography (ECG) have demonstratd failures of several educational strategies related to diagnostic competence for interpretation. It is a low-cost exam and important for detection of cardiac arrhythmias and other pathological alterations. If used correctly this exam can save lives. Objectives: To compare the effect of two ECG teaching methodologies (instructional prompts and self-directed study) on the diagnostic competence of supraventricular arrhythmias among medical students. Materials and Methods: Experimental study in three phases: Initial Evaluation (Phase 1), Training (Phase 2) and Late Evaluation (Phase 3). The sample consisted of 24 undergraduate medical students from the 5th semester in the Faculty of Medicine at the UNIFENAS-BH. During the first phase, the students were gathered in a room, answered to a sociodemographic questionnaire and a self-assessment questionnaire of prior knowledge about the arrhythmias that would be part of the study. After, they were invited to provide the diagnosis of the ECG of 11 tracings. Later, an expository lecture on the electrocardiographic analysis of the cardiac rhythms that would be part of the study (sinus, atrial fibrillation, atrial tachycardia and atrial flutter) was performed. Finally, the students were randomly divided into 2 groups (Group 1 and 2). In Phase 2, Group 1 was guided to report the ECG of the 11 rhythms presented in the expository class through the self-directed study, and Group 2 to report the same rhythms guided by instructional prompts. In Phase 3, all students provided diagnoses of the ECG rhythms for a new group of 11 routes. The primary outcome was the diagnostic accuracy of cardiac rhythms in each phase. Results: Analysis of the 24 students' results showed that the instructional prompt strategy was statistically superior in Phase 3 on the average of the students' scores when providing the rhythm diagnoses (p = 0.034, d.p. 1.1). The grades by groups in the 3 phases presented the following averages: Group 1 (Phase 1 = 3.3 ± 2.7; Phase 2 = 5.3 ± 2.3; Phase 3 = 4.9 ± 2.0) and Group 2 (Phase 1 = 2.2 ± 1.9; Phase 2 = 6.8 ± 2.2: Phase 3 = 6.7 ± 1.1). Conclusions: The use of instructional prompts as a teaching strategy for cardiac rhythm analysis improved the diagnostic accuracy of undergraduate medical students for the arrhythmias studied. This is an easy-to-use strategy that can be considered for teaching heart rhythm disorders